Effects of fiber cross-section shape on thermal comfort properties of polyester interlock fabrics - ARZU Marmaralı (Communications in Development and Assembling of Textile Products, 2023)
In this study, some dimensional and thermal comfort properties, i.e. thermal resistance, water vapor permeability, and air permeability properties of interlock fabrics knitted from different cross-section shaped polyester fibers were investigated. Four polyester yarns of different fiber cross-section shapes (hollow-round, round, triangular, and W-shape) were used to produce the samples. From the results, it was found that the triangular and W-type fibers had higher fabric density values due to the denser and closer fiber settlement. The highest bursting strength value belonged to the sample knitted from hollow-round yarn, which had also the highest yarn-breaking load value. The samples knitted from both round cross-section polyester yarns had significantly higher air permeability and thermal resistance values than the other samples due to the lower fabric density values of these fabrics. On the other hand, the water vapor permeability values of the fabrics from triangular and W-type fibers were slightly higher than the others because of their lower thicknesses.